PERANCANGAN SISTEM INFORMASI PENGELOLAAN DATA SAMPAH BERBASIS PROTOTYPE MENGGUNAKAN FIGMA PADA PT PLN INDONESIA POWER UBP KERAMASAN - Alda Dwi Agustina; Gusmelia Testiana (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of information technology has encouraged various organizations, including electricity supply companies, to adopt information systems that support more effective and efficient data management, including in environmental management aspects. The Environmental Division of PT PLN Indonesia Power UBP Keramasan currently still records non-B3 waste data manually using physical documents and simple spreadsheets, which often causes data duplication, recording errors, lost records, and delays in report preparation. This study aims to design a prototype information system for non-B3 waste data management by utilizing the Figma application as a tool for visualizing the system interface. Data were collected through observation, interviews, and literature study, while the system development applied the prototype model with the stages of communication, planning, modeling, construction, and deployment. The results consist of an interface prototype design comprising a login page, dashboard, non-B3 waste data page, data input page, and a report page equipped with an Excel export feature. The prototype design represents the workflow of recording, storing, and reporting non-B3 waste data in a more structured manner compared to the current manual system. This study concludes that the prototype-based information system design can serve as an initial reference before full implementation, thereby helping the Environmental Division manage non-B3 waste data more accurately, efficiently, and in an integrated manner.